Eduard Dorsch and his unpublished poem on the occasion of Humboldt’s 100th birthday - Andress, Reinhard (HiN – Alejandro de Humboldt en la Red. Revista internacional de estudios humboldtianos, 2018)
AbstractIn 1869, the German-American medical doctor and poet, Eduard Dorsch, wrote a poem read in Detroit on the occasion of Humboldt’s 100th birthday. This article publishes the poem for the first time and explores its context within the life and times of its author.ZusammenfassungIm Jahre 1869 schrieb der deutsch-amerikanische Arzt und Dichter Eduard Dorsch ein Gelegenheitsgedicht, das anlässlich von Humboldts 100. Geburtstag in Detroit vorgelesen wurde. Dieser Artikel veröffentlicht das Gedicht zum ersten Mal und erforscht dessen Kontext im Leben und in der Zeit des Autors.ResumenEn el año 1869, el médico y poeta germanoamericano escribió un poema ocasional leído con motivo del 100º cumpleaños de Humboldt. Este artículo publica el poema por primera vez y explora su contexto en la vida y el tiempo del autor.